Acoustic methods for high‐throughput protein crystal mounting at next‐generation macromolecular crystallographic beamlines. (24th September 2013) - Roessler, Christian G.; Kuczewski, Anthony; Stearns, Richard; Ellson, Richard; Olechno, Joseph; Orville, Allen M.; Allaire, Marc; Soares, Alexei S.; Héroux, Annie
Abstract : To take full advantage of advanced data collection techniques and high beam flux at next‐generation macromolecular crystallography beamlines, rapid and reliable methods will be needed to mount and align many samples per second. One approach is to use an acoustic ejector to eject crystal‐containing droplets onto a solid X‐ray transparent surface, which can then be positioned and rotated for data collection. Proof‐of‐concept experiments were conducted at the National Synchrotron Light Source on thermolysin crystals acoustically ejected onto a polyimide `conveyor belt'. Small wedges of data were collected on each crystal, and a complete dataset was assembled from a well diffracting subset of these crystals. Future developments and implementation will focus on achieving ejection and translation of single droplets at a rate of over one hundred per second.